2017
DOI: 10.1155/2017/7360354
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human Amniotic Mesenchymal Stem Cells into Human Anterior Cruciate Ligament Fibroblast Cells by In Vitro Coculture

Abstract: Anterior cruciate ligament injuries are common in humans, though cellular components of the knee have little regenerative or proliferation potential. This study investigated the differentiation of human amnion-derived mesenchymal stem cells (hAMSCs) into human anterior cruciate ligament fibroblasts (hACLFs) in vitro through induction with bFGF and TGF-β1 with coculture systems. Groups A and B comprised hAMSCs at the 3rd passage cultured with and without bFGF and TGF-β1, respectively; Groups C and D consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…hAMSCs were isolated from six full-term puerperants, and informed consent was obtained from all of the patients prior to their participation. For the isolation of hAMSCs, they were first dissected bluntly from the placenta as previously described 13 . Following this, the amnion samples were washed three times with phosphate-buffered saline (PBS) and transferred to sterile containers at 4°C in a laboratory facility.…”
Section: Isolation and Cultivation Of Hamscsmentioning
confidence: 99%
See 1 more Smart Citation
“…hAMSCs were isolated from six full-term puerperants, and informed consent was obtained from all of the patients prior to their participation. For the isolation of hAMSCs, they were first dissected bluntly from the placenta as previously described 13 . Following this, the amnion samples were washed three times with phosphate-buffered saline (PBS) and transferred to sterile containers at 4°C in a laboratory facility.…”
Section: Isolation and Cultivation Of Hamscsmentioning
confidence: 99%
“…In addition, they do not carry ethical or moral controversies with them 12 . hAMSCs have a multidirectional differentiation capacity as well as an advantage in therapeutic angiogenesis due to the hAMSC root in placenta, which is a vascular tissue 13 . Hence, hAMSCs have been extensively applied in the treatment of bone and spinal traumas and vascular reconstruction surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that hAMSCs expressed vimentin-a marker for MSCs-greatly but hardly expressed cytokeratin 19 (a typical phenotype molecule of human amniotic epithelial cells). Although vimentin was used as the only hAMSC marker, other properties of hAMSCs were confirmed in our previous experiment [35], such as plastic adherence, specific surface antigen (Ag) expression, and multipotent ability to differentiate into osteoblasts, adipocytes, and chondrocytes. After confirming MSC properties in our P3 hAMSC culture lines, we used a lentivirus containing the human FGF-2 gene to transfect the hAMSCs wherein the transfection efficiency was determined via the expression of fluorescence and qRT-PCR.…”
Section: Discussionmentioning
confidence: 77%
“…For this study, placentas were obtained from the Obstetrics Department of the Affiliated Hospital of Zunyi Medical University with informed consent from each patient before operation. In line with a previous research [35], hAMSCs used in this study were isolated from the human placental amniotic membrane of 5 healthy full-term puerperant women by subjecting to enzymatic (Solarbio, China) digestion twice, followed by collagenase type II (Gibco, USA) digestion once. In brief, the isolated amniotic membrane was minced into pieces and digested twice with 0.05% trypsin/0.01% ethylenediaminetetraacetic acid (EDTA) for 30 mins at 37°C, followed by washing the tissue with phosphate buffer solution (PBS) and digestion with 0.75% collagenase type II for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation